Multi-omics revealed rumen microbiota metabolism and host immune regulation in Tibetan sheep of different ages - Sha, Yuzhu; Liu, Xiu; He, Yanyu; Zhao, Shengguo; Hu, Jiang; Wang, Jiqing; Li, Wenhao; Shao, Pengyang; Wang, Fanxiong; Chen, Xiaowei; Yang, Wenxin; Xie, Zhuanhui (Frontiers in Microbiology, 2024)
The rumen microbiota and metabolites play an important role in energy metabolism and immune regulation of the host. However, the regulatory mechanism of rumen microbiota and metabolite interactions with host on Tibetan sheep's plateau adaptability is still unclear. We analyzed the ruminal microbiome and metabolome, host transcriptome and serum metabolome characteristics of Tibetan sheep at different ages. Biomarkers Butyrivibrio, Lachnospiraceae_XPB1014_group, Prevotella, and Rikenellaceae_RC9_gut_group were found in 4 months, 1.5 years, 3.5 years, and 6 years Tibetan sheep, respectively. The rumen microbial metabolites were mainly enriched in galactose metabolism, unsaturated fatty acid biosynthesis and fatty acid degradation pathways, and had significant correlation with microbiota. These metabolites further interact with mRNA, and are co-enriched in arginine and proline metabolism, metabolism of xenobiotics by cytochrome P450, propanoate metabolism, starch and sucrose metabolism, gap junction pathway. Meanwhile, serum metabolites also have a similar function, such as chemical carcinogenesis − reactive oxygen species, limonene and pinene degradation, and cutin, suberine and wax biosynthesis, thus participating in the regulation of the body's immune and energy-related metabolic processes. This study systematically revealed that rumen microbiota, metabolites, mRNA and serum metabolites of Tibetan sheep were involved in the regulation of fermentation metabolic function and immune level of Tibetan sheep at different ages, which provided a new perspective for plateau adaptability research of Tibetan sheep at different ages.